Pengaruh Manajemen Hubungan Pelanggan Terhadap Kepuasan Pelanggan Pada Pengguna Gopay - Marlina Anggraeni; Kartika Ameliana; Nurul Azizah; Abdul Yusuf (Peneliti.net, 2022)
This study aims to determine how much the customer relationship management variable (X) affects the customer satisfaction variable (Y). It focuses on one of the electronic payment GoPay. The research method used is descriptive analysis and verification. The sample in this study was 204 GoPay users in Karawang. How to spread questionnaires and literature studies. To analyze the data the researches used regression analyze and a valid value correlation analysis is 0.173 and the reliability value is 0.85. results in this study indicate that there is an influence between customer relationship management on customer satisfaction of GoPay users by 55% and 45% is affacted by other variables that researchers don’t use.